Antithrombotic therapy for ischaemic stroke patients with AF/RHD in West China daily practice. (October 2015) - Wang, Deren; Liu, Junfeng; Hao, Zilong; Liu, Ming; Tan, Ge; Jiang, Xiaoqun; Tao, Wendan
<x content-type="archive" xml:space="preserve">Abstract</x> Background and Objective: Although, current evidence-based guidelines advocate anticoagulation as a strong recommendation in IS patients with AF/RHD, the underuse of anticoagulation in IS patients with AF/RHD has been found in clinical practice worldwide. Nevertheless, there was little information about implementation of antithrombotic therapy to prevent stroke for patients with AF and/or RHD in daily practice in West China. Our study determined to clarify the patterns, adherence and comparative effect of antithrombotic treatment during 1-year follow-up in IS patients with AF and/or RHD. Method: Consecutive patients with acute IS and AF/RHD admitted to Department of Neurology, West China Hospital from November 2010 to October 2011 were included in the study. Results: 155 consecutive patients were analysed in this study. One hundred thirteen patients have been diagnosed as AF and/or RHD before admission. Of these, 49 (43.4%) patients were receiving antithrombotic therapy before the time of admission, including nine (8.0%) patients receiving warfarin. At 12 months after stroke onset, 109 (81.3%) patients were on antithrombotics, and 46 (34.3%) patients were on warfarin alone. The persistence rate of warfarin use at 1 year was 77.8%. Moreover, there were 80 (81.6%) patients never starting to use warfarin. Compared with no antithrombotic therapy, anti-platelets and warfarin reduced death risk significantly during 1-year after stroke onset (P = 0.005). Conclusion: Our study suggests that overall real-world use of warfarin in IS patients with AF and/or RHD is low before and after admission in West China. Implementation study on this respect should be conducted in this area to improve the daily practice.